ANALISIS FINANSIAL PENGEMBANGAN USAHATANI LADA DI KECAMATAN ABUNG TENGAH KABUPATEN LAMPUNG UTARA - Risca Fara Midta Sari; Fembriarti Erry Prasmatiwi; Zainal Abidin (Lampung University, 2022)
The research aims to find out financial and sensitivity analysis of pepper farming. This research was conducted in Gunung Besar Village and Sri Bandung Village, Abung Tengah Subdistrict, North Lampung District. Respondents consist of thirty pepper farmers selected randomly by using stratified random sampling. The first goal is analyzed using financial and sensitivity analysis. The study shows that NPV, IRR, Net B/C, Gross B/C, and payback period of pepper farming are financially profitable and feasible to be developed. The value of NPV is bigger than 0, the value of Gross B/C and Net B/C are bigger than 1, the value of IRR is bigger than interest rate (9.95%) and the value of payback period is less than 10 years. The sensitivity analysis shows if the production cost increases to 7.26 percent, if the quantity decreases to 34 percent and if the output price decreases to 28 percent, the pepper farming will be sensitive and pepper farming still financially profitable and feasible.Key words: farming, financial, pepper, sensitivity